Verbalization of the Concept of «God» in Stepan Rudansky’s Spivomovky (Linguostylistic Studies, 2015)
The article deals with the language expressive means of the concept «God» in S. Rudansky’s comic spivomovka (a short humorous or satirical verse based on aphorism, proverb, saying, joke) as one of the central problems in the Ukrainian religious and linguistic world pictures of. This author was traditionally considered to be «a passionate atheist», thereby a great number of his work was devoted to religious subjects. Based on the analysis it is proved that the humorous image-concept «God» is created as a result of the peripheral senses actualizing, brings him to the other characters, the simple peasants. Such an image-concept of God is the extension of Ukrainian humorous culture traditions, mostly developed in the seminary poetry during the XVI–XVII century. Rare verbalization of the Son of God image in the Ukrainian jokes and, accordingly, in S. Rudansky’s spivomovky indicates Christocentric feature of the Ukrainian culture. Key words: verbalization, image-concept, connotation, spivomovka, sense. References